2002
DOI: 10.1021/ja0257772
|View full text |Cite
|
Sign up to set email alerts
|

Exciplex Intermediates in Photoinduced Electron Transfer of Porphyrin−Fullerene Dyads

Abstract: The photoinduced electron transfer in differently linked zinc porphyrin-fullerene dyads and their free-base porphyrin analogues was studied in polar and nonpolar solvents with femto- to nanosecond absorption and emission spectroscopies. A new intermediate state, different from the locally excited (LE) chromophores and the complete charge-separated (CCS) state, was observed. It was identified as an exciplex. The exciplex preceded the CCS state in polar benzonitrile and the excited singlet state of fullerene in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(142 citation statements)
references
References 63 publications
9
131
1
1
Order By: Relevance
“…[29][30][31][32] Deceleration effect of higher fullerene, i.e., C 70 , for CR was also observed for porphyrin-C 70 dyad vs porphyrin-C 60 dyad with the same spacer. 55,84 On the basis of the experimental results, we proposed, for the first time, that of fullerenes are much smaller than those of typical two-dimensional acceptors. 51 The photoinduced CS process in the Marcus normal region becomes fast with decreasing the value, whereas the CR process in the Marcus inverted region becomes slow with decreasing the value.…”
Section: Introductionmentioning
confidence: 90%
“…[29][30][31][32] Deceleration effect of higher fullerene, i.e., C 70 , for CR was also observed for porphyrin-C 70 dyad vs porphyrin-C 60 dyad with the same spacer. 55,84 On the basis of the experimental results, we proposed, for the first time, that of fullerenes are much smaller than those of typical two-dimensional acceptors. 51 The photoinduced CS process in the Marcus normal region becomes fast with decreasing the value, whereas the CR process in the Marcus inverted region becomes slow with decreasing the value.…”
Section: Introductionmentioning
confidence: 90%
“…[36,37] We have reported that in a similar zinc porphyrin± C 60 system a charge-separated state is formed via an exciplex in polar solvents, whereas in a similar free-base porphyrin±C 60 system only the charge-separated state is produced in polar solvents. [38,39] Based on these results, two different mechanisms were proposed for the photocurrent generation in self-assembled monolayers of porphyrin±C 60 devices. The low quantum yield of the formation of a charge-separated state in the Au/1/MV 2+ /Pt device results in poor photocurrent generation, whereas the direct, efficient formation of a charge-separated state with a longer lifetime in the Au/2/MV 2+ /Pt device leads to a pronounced increase in the photocurrent generation.…”
Section: Introductionmentioning
confidence: 99%
“…The low quantum yield of the formation of a charge-separated state in the Au/1/MV 2+ /Pt device results in poor photocurrent generation, whereas the direct, efficient formation of a charge-separated state with a longer lifetime in the Au/2/MV 2+ /Pt device leads to a pronounced increase in the photocurrent generation. [38,39] …”
Section: Introductionmentioning
confidence: 99%
“…3) affords the longer CS lifetime as compared with other zinc chlorin-fullerene dyads with the longer spacers. [36][37][38][39][40] A deoxygenated PhCN solution containing ZnCh-C 60 gives rise upon a 388 nm laser pulse to a transient absorption maximum at 460 nm due to the singlet excited state of ZnCh. 36 The decay rate constant was determined as 1:0 Â 10 11 s À1 , which agrees with the value determined from the fluorescence lifetime measurements.…”
Section: -17mentioning
confidence: 99%